EVALUASI PERANGKAT PEMBELAJARAN IPA SMP TOPIK KLASIFIKASI MAKHLUK HIDUP MENGGUNAKAN MODEL INKUIRI - Tri Setyowati; Muhammad Zaini; Aminuddin Prahatama Putra (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2019)
The scientific literacy skills of Indonesian students are still low. This condition encourages the government to improve the ability to solve problems, namely by issuing Permendikbud Number 65 of 2013 concerning the standards for the process of primary and secondary education, including the development of the domain of attitudes, knowledge, and skills. This development research aims to produce science learning tools on the topic of classification of living things in class VII of the SMP Negeri which are valid, practical and effective. Development research refers to the device development model with phases 1) Identifying problems, 2) Describing objectives, 3) Designing and developing devices, 4) Performing tests, 5) Evaluating test results, and 6) Communicating test results. Data was collected using instruments and evaluation questions. All data collected was analyzed descriptively. The results showed that the learning device was declared valid. Practical learning tools are used based on the results of the lesson plan implementation and student responses. Learning tools are also effectively based on results 1) cognitive assessment 2) psychomotor, social, and spiritual assessment, 3) critical thinking assessment, 4) student activity on teaching and learning activities and, 5) teacher response to teaching and learning activities.